Comment on 'Finite-time synchronization of Lorenz chaotic systems: theory and circuits'. (3rd March 2015) - Luo, Runzi; Zeng, Yanhui
Abstract: In a recent paper, Louodop et al (2013 Phys. Scr. 88 045002 ), a family of feedback couplings which accomplish the synchronization of Lorenz chaotic systems was proposed based on Lyapunov stability theory. We point out that there is an error which is fundamental to the main result of the paper. Furthermore, the controller is complex and can be replaced by, where = .